REVERSAL OF GEOMETRIC PROBLEMS AS A MEANS OF DEVELOPING THE THINKING OF FUTURE MATHEMATICS TEACHERS - Shmigirilova И.; Rvanova А.; Beloshistova Я.; Dutkin М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The school mathematics teacher is faced with task of not only ensuring the mathematical preparation of students sufficient for continuing education, but also developing them intellectually, forming their mathematical style of thinking. In order for teacher to be able to cope with this task, he himself must have a sufficient level of mathematical thinking. The purpose of this article is to update the importance of using method of inversion of geometric problems as an effective means of developing mathematical thinking of mathematics students. The results of theoretical and empirical research presented in article confirmed that this type of productive educational and cognitive activity of future mathematics teachers allows them to master mathematical theory, develops their mathematical thinking, cognitive independence, communication skills and, ultimately, forms qualities necessary for a modern mathematics teacher.